Analysis of the feasibility of reverse logistics in footwear production employing technologies RFID and Cloud Computing - Schreiber, Dusan; Sander, Silaine Carini; Becker, Vilson José (Revista de Administração da UFSM, 2023)
Purpose: To analyze the feasibility of a reverse logistics process in the footwear production, using two technologies from industry 4.0 – RFID and Cloud Computing. Methodology: A case study was carried out in a large footwear industry, located in southern region of the country; qualitative approach, with data collection through semi-structured interviews, documental research (internal digital records/intranet) and non-participant systematic observation. Findings: The empirical data showed that the two technologies analyzed, RFID and Cloud Computing, are already implemented in some operations in the company, and offer technical conditions to operationalize the reverse logistics process. Originality/value: Industrial operations promote various actions to adapt to environmental standards, both legal ones, already in force, and the recommended ones, resulting from pressure from society, increasingly aware of the need for changes in processes that negatively impact the environment. Among these actions, the adoption of reverse logistics stands out, considered one of the structuring axes of the National Solid Waste Policy, enacted in 2010. This analysis, regarding the contribution of these two technologies is justified by intentions of footwear companies to employ these technologies in the manufacturing process.